Prospects of TiO2-based photocatalytic degradation of microplastic leachates related disposable facemask, a major COVID-19 waste - Rex M, Camil; Mukherjee, Amitava (Frontiers in Nanotechnology, 2022)
COVID-19 is one of the serious catastrophes that have a substantial influence on human health and the environment. Diverse preventive actions were implemented globally to limit its spread and transmission. Personnel protective equipment (PPE) was an important part of these control approaches. But unfortunately, these types of PPE mainly comprise plastics, which sparked challenges in the management of plastic waste. Disposable face masks (DFM) are one of the efficient strategies used across the world to ward off disease transmission. DFMs can contribute to micro and nano plastic pollution as the plastic present in the mask may degrade when exposed to certain environmental conditions. Microplastics (MPs) can enter the food chain and devastate human health. Recognizing the possible environmental risks associated with the inappropriate disposal of masks, it is crucial to avert it from becoming the next plastic crisis. To address this environmental threat, titanium dioxide (TiO2)-based photocatalytic degradation (PCD) of MPs is one of the promising approaches. TiO2-based photocatalysts exhibit excellent plastic degradation potential due to their outstanding photocatalytic ability, cost efficiency, chemical, and thermal stability. In this review, we have discussed the reports on COVID-19 waste generation, the limitation of current waste management techniques, and the environmental impact of MPs leachates from DFMs. Mainly, the prominence of TiO2 in the PCD and the applications of TiO2-based photocatalysts in MPs degradation are the prime highlights of this review. Additionally, various synthesis methods to enhance the photocatalytic performance of TiO2 and the mechanism of PCD are also discussed. Furthermore, current challenges and the future research perspective on the improvement of this approach have been proposed.